Diagnostic and prognostic value of miR-1 and miR-29b on adverse ventricular remodeling after acute myocardial infarction – The SITAGRAMI-miR analysis. (1st October 2017) - Grabmaier, U.; Clauss, S.; Gross, L.; Klier, I.; Franz, W.M.; Steinbeck, G.; Wakili, R.; Theiss, H.D.; Brenner, C.
Abstract: Background: MicroRNAs (miRs) have shown to exert fibrotic and anti-fibrotic effects in preclinical models of acute myocardial infarction (AMI). The aim of this study was to evaluate miR-1, miR-21, miR-29b and miR-92a as circulating biomarkers for adverse ventricular remodeling (AVR) in post-AMI patients. Methods: Plasma levels of miR-1, miR-21, miR-29b and miR-92a were measured in 44 patients of the SITAGRAMI trial population at day 4, day 9 and 6 month after AMI and in 18 matched controls (CTL). MiR expression patterns were correlated with magnetic resonance imaging (MRI) parameters for AVR (absolute change (Δ) in infarct volume (IV), left ventricular ejection fraction (LVEF) and left ventricular end-diastolic volume (LVEDV) between day 4 and 6 months after AMI) and a combined cardiovascular endpoint. Results: Expression of miR-1, miR-21 and miR-29b but not miR-92a was increased in AMI vs. CTL cohort showing highest miR levels at d9. However, only miR-1 and miR-29b levels significantly correlated with ΔIV and showed a trend for correlation with ΔLVEF. Only miR-29b levels at day 9 correlated with ΔLVEDV at 6-month follow-up. There was no correlation of miR levels with an adverse outcome. Conclusion: Mir-1 and miR-29b plasma levels post-AMI correlate with IV changes. In addition, miR-29b levels are associated with changes of LVEDV over time. These results provide insights into the role of miRs as diagnostic AVR surrogate markers. Further large scale clinical trials will be needed to evaluate the real prognostic relevance of these miRs with respect to a clinical implication in the future.